Mtalaa wa isimu : fonetiki, fonolojia na mofolojia ya Kiswahili - Mgullu, Richard S. (Richard Songelaeli) (Nairobi : Longhorn Publishers, 1999)
Study of phonetics, phonology and morphology of Swahili.
Includes bibliographical references (p. [235]-239) and indexes.
In Swahili.
Keywords: Swahili language -- Phonetics; Swahili language -- Phonology; Swahili language -- Morphology